Data Transmission Performance Analysis on the Usage of ZLib Compression over Secure Shell Protocol - Panca, Billy Susanto; Wijaya, Chandra (IJTB (International Journal of Technology And Business), 2019)
In a scope of data communication through the network, security and communication performance are needed to be considered. However, security and performance are contrary to each other. If we choose to improve security aspect then the performance will decrease, and vice versa. The data communication performance is affected by network bandwidth and throughput, otherway we can improve data transmission performance by reducing the file size before we send it through the network by using compression algorithm. The compressed bits will be sent through the secured network by using secure shell protocol. However, the usage of compression might increase the processing delay which affect transmission performance. The testing will be conducted by measuring communication quality of the result by using unification of secure shell protocol and Zlib compression algorithm. In this research, we designed and made a software that allows data exchanging with considering the aspect of efficiency and security. The testing will be conducted to determine the impact of the unification of secure shell protocol and compression algorithm on high performance network.